(untitled) (Journal of the Sylhet Agricultural University, 2025)
Salinity is a significant barrier that inhibits crop production in salt-affected areas as in the southern region of Bangladesh. Maize (Zea mays L.), is the third most major cereal crop that has shown decreased plant growth and production potential under saline conditions. Furthermore, salinity affects both plant growth and production. Hybrid maize has been recently introduced to the cropping systems of southern Bangladesh to enhance cropping intensity and productivity. The experiment was conducted at the Botiaghata, Khulna (AEZ-11) during the Robi season of 2022-23 to determine hybrid salt tolerant lines for maximizing maize yield and its utilize thousands of hectares of unproductive land and dikes of shrimp farms. Fifteen advanced lines of hybrid maize were evaluated in the study. The experiment was laid out in randomized compete block design with three replications. The highest grain yield was found in E-34 x BIL-211 was 11.37 t ha-1 and which was followed by Pinacle-3 x BIL-211 (9.71 t ha-1) and BIL-79 x Pinacle-16 (9.09 t ha-1). The lowest yield was found from BIL-106 x CML-480 (3.53 t ha-1). It is suggested that E-34 x BIL-211 can be grown in the southwestern coastal region of Bangladesh. J. Sylhet Agril. Univ. 12(1): 72-83, 2025